Proton magnetic resonance spectroscopy in the evaluation of infiltration zone of cerebral alveolar echinococcosis - Wang, Jian; Yao, Wei-Hong; Yi, Ba-Nu; Liu, Shen; Zhang, De-Qing; Jiang, Chun-Hui; Zhang, Li-Min; Niu, Jun-Qiao; Jia, Wen-Xiao; Wen, Hao (Chinese medical journal, 2012)
Background Cerebral alveolar echinococcosis （CAE） grows infiltratively like a malignant tumor, causing great harm to the human body. It is possible to display mass lesions of CAE using various imaging systems, but regarding the infiltrating proliferation active regions, it is difficult to evaluate its actual range using conventional magnetic resonance imaging （cMRI）. This research focused on proton magnetic resonance spectroscopy （1HMRS） techniques to find the mass and infiltration zone of CAE. We explored the marginal zone （MZ） of CAE nearly close to the actual infiltrating scope, to provide reliable images for clinical purposes, to overcome shortcomings of cMRI, to formulate beneficial clinical surgical plans and assess prognosis. Methods Between September 2005 and May 2011, 15 patients who were suffering from CAE （36 effective lesions altogether） were examined by 1HMRS at the first affiliated hospital of Xinjiang Medical University. Multi-voxel 1HMRS was acquired with a 1.5T MRI scanner. Concentrations and the ratios of the metabolites of CAE were calculated. Furthermore, changes in the concentrations of the metabolites containing N-acetyl-aspartic-acid （NAA）, choline （Cho）, creatine （Cr）, lipids and lactate （Lip＋Lac） and the ratios of Cho/Cr, NAA/Cr, （Lip＋Lac）/Cr were compared in the substantial region, 0-10 rnm MZ, and 11-20 mm MZ of the infiltration zone, as well as the corresponding contralateral part of the normal brain parenchyma area （control group）. Results In this study, the ratios of Cho/Cr in the substantial region, 0-10 mm MZ of infiltration zone and the control group were 1.78＋0.70, 1.90＋_0.54, and 0.78＋_0.15, respectively; the ratios of NAA/Cr were 1.60＋0.20, 1.80＋0.42, 2.24＋_0.86, respectively; the ratios of （Lip＋Lac）/Cr were 25.69＋_13.84, 25.18＋16.03, and 0.61 ＋0.15, respectively. From the control group, 11-20 mm MZ to 0-10 mm MZ and the substantial region of CAE, the concentrations of the metabolites showed that NAA and Cho decreased gradually and markedly. But （Lip＋Lac） increased gradually and markedly. The ratios of Cho/Cr and NAA/Cr, （Lip＋Lac）/Cr were statistically significant （P 〈0.0083） between the substantial region and the control group, as well as between the 0-10 mm MZ and the control group. The ratios of Cho/Cr and NAA/Cr, （Lip＋Lac）/Cr displayed no statistically significant differences （P 〉0.0083） between the substantial region and the 0-10 mm MZ. Conclusions There was a pathological spectrum surrounding the infiltration zone of CAE. Multi-voxel IHMRS has great clinical value for discerning the main lesion and the infiltration zone of CAE.